Stability of the explant in the in vitro proliferation of axillary shoots of the biznaga - Villavicencio-Gutiérrez, Eulalia Edith; Arellano-Ostoa, Gregorio; Carranza-Pérez, Miguel A. (Revista Mexicana de Ciencias Agrícolas, 2022)
To conserve ex situ, promote the use and enhancement of native germplasm of ornamental interest such as T. viereckii subsp. major, a species at risk Pr, the present research was proposed with the aim of regenerating this species in the Plant Tissue Culture Laboratory (LCTV) of the Saltillo CIRNE-INIFAP Experimental Field considering the stability of the explant during subsequent subcultures, determine the type and concentration of phytohormones and the best cytokinin-auxin ratio that most influence the in vitro multiplication stage. The intermediate segments of the stem (SIT) obtained from vitroplants was used as an explant. From 2017 to 2019, the multiplication stage was evaluated using the Murashige-Skoog medium (MS; Murashige and Skoog, 1962) at 50% of its macrosalts. A completely randomized experimental design with factorial arrangement was used to evaluate two cytokinins: 6-benzyl aminopurine (BAP) and 6-furfuryl aminopurine (KIN) at four concentrations 2.5, 5, 7.5 and 10 mg L-1 in interaction with two auxins: naphthaleneacetic acid (NAA) and indole butyric acid (IBA) in a cytokinin-auxin ratio of 10:1. In total, 16 treatments were evaluated, establishing five SIT/bottle with 10 repetitions/treatment. This evaluation was repeated five times by means of subcultures, evaluating the number of shoots/explant (Nb) and the shoot height (Ab, mm) every ten weeks. The analysis of variance (Anova) showed that there was stability of the explant during the subcultures, maintaining a similar multiplication rate for more than three years, an important effect for intensive multiplication. When analyzing the treatments as independent effects in the Tukey mean test (p≤ 0.05), the interactions BAP: IBA and KIN: IBA with concentrations of 5 mg L-1 BAP + 0.50 mg L-1 IBA and 2.5 mg L-1 KIN + 0.25 mg L-1 IBA were selected as the treatments that induce shoots with a multiplication rate of 9.25 shoots/explant with an Ab of 6.73 mm.
Keywords: in vitro culture; growth regulators; ornamental cacti